Multi-criteria analysis for secondary school site selection in Bertam, Gua Musang, Kelantan / Farhan Rasydan Romzi and Fatin Nabila Abdullah - Abdullah, Fatin Nabila; Romzi, Farhan Rasydan (Universiti Teknologi MARA (UiTM), 2024)
This project explores the suitability of a potential site to establish a secondary school in Gua Musang, Kelantan, Malaysia. Using ArcGIS Pro software and the tools found in it made this project successfully completed. This study also evaluates various criteria including safety, demographic suitability and so on. Data collected from PlanKelantan and analysis done to identify optimal locations that meet educational standards and community needs.